Dissipativity of Nonlinear 2D Systems∗. Issue 11 (2015) - Emelianova, Julia; Emelianov, Mikhail; Pakshin, Pavel; Galkowski, Krzysztof; Rogers, Eric
Abstract: The paper considers nonlinear 2D continuous-time systems described by a statespace model of the Roesser form and nonlinear differential repetitive process. The property of exponential dissipativity is introduced and then a particular case of this property, termed exponential G passivity is used, together with a vector storage function, to develop a new method for output feedback based control law design.